Application of web design techniques and best practices in implementing web development, maintenance and enhancement of RUBi websites and web application systems - Tshabalala, Thulani (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The popularity of the web has seen various fields, such as the sciences taking advantage of this resource to further their scientific endeavours. This has seen science groups moving into developing websites and web applications, and such a group is the Research Unit in Bioinformative (RUBi). With the use of the web, the development and maintenance of whatever web-related tools become inevitable, given the continuous changes in the web space. This continuous evolution of web development and maintenance will come with techniques, principles and standards which will not only enable faster development of web entities but also ensure that modern hardware, fulfilment of the requirements to use such hardware and modern concepts are incorporated into forming web tools that enable such progression. Furthermore, introducing the previously mentioned progress of the web becomes an essential part of its development and maintenance. This paper did implement the processes of progressing the web using the technique of documentation and version control systems. The web development for the COVIDRUG website was done for the Covidrug-Africa Consortium (COVIDRUG) using the Django webdevelopment framework. The RUBi website and the MDM-Task we band the Job Management System (JMS) web applications were maintained for the maintenance aspect. Archives brought value regarding the traceability it provides of the various web-related aspects. The development showed a website's potential value, particularly for research groups. The maintenance carried out showed how different techniques and approaches could be used in different maintenance prospects to achieve set objectives. The development and maintenance resulted in websites and web applications that have the features stated in their respective maintenance plans.
Keywords: Web design; Web applications; Bioinformatics; Django; Web servers Computer programs